Clinical and dermatoscopic features of porokeratosis palmaris et plantaris - Satish Udare; Karishma Hemmady (Wolters Kluwer Medknow Publications, 2016)
A dermatoscope is an important tool in a dermatologist's armamentarium as it can eliminate the need for a biopsy in a wide array of conditions. Porokeratosis was described by Mibelli and Respighi in 1893, as a disorder of keratinization which on the basis of distribution patterns was described as five clinical variants that portrayed a coronoid lamella on histopathology. We describe a case of asymptomatic, long-standing palmar and plantar pits, which on dermatoscopy showed features suggestive of porokeratosis, which was later reconfirmed by histopathologic sections. This report depicts diagnostic features of porokeratosis and obviates the need for invasive procedures for its diagnosis.